The use of infrared skin temperature measurements for monitoring heat stress and animal welfare - Yadav, Brijesh; Singh, Gyanendra; WANKAR, ALOK KUMAR (Indian Journal of Dairy Science, 2017)
The present investigation was carried out to use body surface temperature as an alternate to measurement of rectal temperature for monitoring heat stress and animal welfare. Four non-pregnant dry crossbred cattle were exposed together to three treatment temperatures (25, 35 and 40Â°C) with a relative humidity of 40-50%, housed in the climatic chamber to simulate different environmental heat stress conditions. The animals were exposed to each temperature for 5 hours/day from 10:00 to 15:00 hours for 21 days. The respiratory rate (RR), rectal temperature (RT) and pulse rate (PR) were recorded at 09:30 hours (before exposure) and 15:00 hours (after exposure) every day. The surface temperatures (ST) of the fore leg, head, neck, lumbar, thigh and hind leg were recorded before and after exposure at five days interval (day 1, 6, 11, 16 and 21) with the help of infra-red digital thermometer. The RT, RR and PR increased significantly (P